PERENCANAAN BAHASA DI INDONESIA BERBASIS TRIGLOSIA - Gufran Ali Ibrahim; Luh Anik Mayani (Linguistik Indonesia, 2018)
For regions or countries with language plurality, which gives impact to cultural plurality, language planning becomes a complex matter. This study proposes concepts on language planning which can be applied in multilingual countries like Indonesia. Based on literary research on language situations in some countries, this study describes the language situation in those countries and compares it the language situation in Indonesia. The conclusion is that the implementation of language planning in Indonesia needs various strategies; there is no single strategy which can be well applied for the whole linguistic situation in the country. Language planning in Indonesia should be started by corpus planning as a strategy to preserve local vernaculars from language endangerment. The next step is determining regulation in order to divide the domains of language use: (1) the use of Indonesian language and local vernacular(s)/colloquial(s) in diglossic regions and (2) the use of Indonesian language, the “intermediate” language and local vernaculars(s) in triglossic regions.